2011
DOI: 10.1007/s12070-011-0144-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Repair of Lateral Sphenoid Recess Cerebrospinal Fluid Leaks

Abstract: Endoscopic repair of anterior cranial base has been widely reported. However there is still no uniformity in the technique of endoscopic repair of lateral sphenoid cerebrospinal fluid (CSF) leaks. To highlight the management of CSF leak or encephalocele in the lateral sphenoid recess and relate our experiences. We retrospectively reviewed the medical records of all our patients who underwent an endoscopic repair of CSF leaks in the lateral sphenoid recess during the period from September 2003 to January 2010 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…They also presented four of their representative cases, with no recurrent CSF leak after endoscopic repair. Kirtane et al [ 13 ] presented their series of 15 lateral sphenoid CSF leaks, all of which were repaired successfully at the first attempt. Interestingly, their series included seven male subjects and eight female subjects.…”
Section: Discussionmentioning
confidence: 99%
“…They also presented four of their representative cases, with no recurrent CSF leak after endoscopic repair. Kirtane et al [ 13 ] presented their series of 15 lateral sphenoid CSF leaks, all of which were repaired successfully at the first attempt. Interestingly, their series included seven male subjects and eight female subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have achieved a high long-lasting closure rate without intracranial pressure recording and treatment. 4,11,35,[36][37][38][39] Other authors have found that uncontrolled intracranial pressure and obesity account for the recurrence. 10,12,[40][41][42][43] Woodworth et al reported that three patients with a failed cerebrospinal fluid closure had a documented ventriculoperitoneal shunt malfunction, suggesting that elevated intracranial pressure contributed to the recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar puncture is an invasive, uncomfortable procedure which may rarely be complicated by pneumocephalus and meningitis. Several authors have achieved a high long-lasting closure rate without intracranial pressure recording and treatment 4 , 11 , 35 , 36 39 . Other authors have found that uncontrolled intracranial pressure and obesity account for the recurrence 10 , 12 , 40 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Kirtane et al performed uncinectomy, anterior and posterior ethmoidectomy, cutting off posterior end of middle turbinate, widening of sphenoidotomy laterally to reach lateral recess, and Hadad flap for covering the defect. 11 El-Tarabishi et al used four-handed two nostrils endoscopic trans-sphenoidal approach. 9 Superior turbinate was resected, middle turbinate sacrificed partially, and rostrum and posterior 1 cm of nasal septum sacrificed.…”
Section: Discussionmentioning
confidence: 99%